The influence of tourist motivation and cultural heritage attributes on tourist satisfaction of homestay programme - Sofinah Yusof; Amran Harun; Syed Azizi Wafa Syed Khalid Wafa; Balvinder Kaur Kler; Mohd Rizwan Abd Majid (Penerbit UMS, 2015)
Tourist satisfaction is significantly important especially in the context of Homestay Programme. This study seeks to understand the influence of tourist motivation and cultural heritage attributes factors towards tourist satisfaction. In this study, tourist motivation is a multidimensional variable comprised of novelty seeking, social, mastery/competence and intellectual. Whilst cultural and heritage is conceptualized to have four attributes namely general tour attraction, culture attraction, recreational experience and local services. Local and foreign visitors who had participated in Homestay Programme in Labuan, East Malaysia were interviewed for the study. The Homestay Programme in Labuan was selected due to the fact that visitors had been gradually decreasing since 2008. Thus, it was proposed that tourist satisfaction with the programme in the area be examined. The study’s results demonstrated that within tourist motivation, only intellectual attribute was found to have a significant relationship with tourist satisfaction, whereas for cultural heritage, it was found that cultural attractions, experience of recreational and local services have a significant relationship with tourist satisfaction. The findings hold significant implications for the marketing strategies of homestay operators particularly in Labuan, Sabah as how to develop and position their offerings in a competitive tourism industry.